PENGARUH KETEPATAN WAKTU DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PERCETAKAN CV. RAI GRAFIKA MEDAN - Farida Hanum Nasution; Yurmaini Yurmaini; Dewi Sundari Tanjung (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This research aims to analyze the influence of Timeliness and Product Quality on Consumer Satisfaction at CV. Rai Grafika Medan Printing. This research is quantitative. The population in this study is the consumers of CV. Rai Grafika Medan. The population includes customers of CV. Rai Grafika Medan, totaling 150 people. The sample consists of 60 respondents. Type and source of data (primary data and secondary data). Data collection methods (observation, interviews, documentation study, questionnaires). Data analysis techniques (validity test, reliability test, classical assumption test (normality test, multicollinearity test), hypothesis testing (multiple linear regression, t-test, F-test, determination test). Research results where, from the t-test results, it was obtained that Ha is accepted, indicating that there is an influence of timeliness on customer satisfaction at CV. RAI Grafika Medan. Indicating that there is an influence of product quality on customer satisfaction at CV. RAI Grafika Medan. From the t-test results, it was obtained that Ha is accepted, meaning it is significant, indicating that there is an influence of product quality on customer satisfaction at CV. RAI Grafika Medan. Products from the consumer's perspective are a matter that has its own scope and is different from quality from the producer's perspective when marketing a product that is already known for its quality. It can be concluded that, partially, timeliness affects consumer satisfaction at CV. RAI Grafika Medan. Partially, product quality affects consumer satisfaction at CV. RAI Grafika Medan.